Effect of 0.01% atropine combined with orthokeratology lens on axial elongation: a 2-year randomized, double-masked, placebo-controlled, cross-over trial - Li, Binbin; Yu, Shiao; Gao, Shasha; Sun, Guangli; Pang, Xuena; Li, Xiuhong; Wang, Ming; Zhang, Fengyan; Fu, Aicun (Frontiers in Medicine, 2024)
Purpose To evaluate the effect of 0.01% atropine combined with orthokeratology (OK) lens on axial elongation in schoolchildren with myopia. Methods Sixty children aged 8–12 years with spherical equivalent refraction (SER) from -1.00D to -4.00D in both eyes were enrolled in this randomized, double-masked, placebo-controlled, cross-over trial. Children who had been wearing OK lenses for 2 months were randomly assigned into combination group (combination of OK lens and 0.01% atropine) for 1 year followed by control group (combination of OK lens and placebo) for another 1 year or vice versa. This trial was registered in the Chinese Clinical Trial Registry (Number: ChiCTR2000033904, 16/06/2020). The primary outcome was changes in axial length (AL). Data of right eyes were analyzed. Results There were statistically significant differences in the changes in AL between combination and control groups after generalized estimating equation model adjusting for age and baseline SER (p = 0.001). The mean axial elongation difference between combination and control groups was 0.10 mm in the first year (0.10 ± 0.13 mm vs. 0.20 ±0.15 mm; p = 0.01), and 0.09 mm in the second year (0.22 ± 0.10 mm vs. 0.13 ± 0.14 mm; p = 0.01), respectively. The mean axial elongation difference of two groups in the first year was similar to that in the second year during the cross-over treatment. Conclusion In central Mainland China in myopic children, the treatment of combination therapy is more effective than single OK lens in controlling axial elongation.